2022
DOI: 10.1186/s13054-022-03928-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of platelet transfusion on outcomes in trauma patients

Abstract: Background Trauma-induced coagulopathy includes thrombocytopenia and platelet dysfunction that impact patient outcome. Nevertheless, the role of platelet transfusion remains poorly defined. The aim of the study was 1/ to evaluate the impact of early platelet transfusion on 24-h all-cause mortality and 2/ to describe platelet count at admission (PCA) and its relationship with trauma severity and outcome. Methods Observational study carried out on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…In patients with MT, early platelet transfusion within 4 h was associated with lower rate of multiorgan failure and mortality within 30 days post-injury, although with a higher rate of ventilator-associated pneumonia and wound infections [ 261 ]. Similarly, in a large trauma database early platelet transfusion within 6 h was associated with decreased 24 h mortality both in patients with massive and non-massive transfusion [ 262 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with MT, early platelet transfusion within 4 h was associated with lower rate of multiorgan failure and mortality within 30 days post-injury, although with a higher rate of ventilator-associated pneumonia and wound infections [ 261 ]. Similarly, in a large trauma database early platelet transfusion within 6 h was associated with decreased 24 h mortality both in patients with massive and non-massive transfusion [ 262 ].…”
Section: Resultsmentioning
confidence: 99%
“…While a low platelet count has been consistently associated with both morbidity and mortality in trauma patients, the threshold and timing of platelet transfusion remains controversial [ 6 ]. Although the platelet count at admission was found to be a biomarker for trauma severity and predictive of outcome, including bleeding intensity and transfusion requirements [ 262 ], platelet counts are frequently within the normal range at hospital admission, but may decrease sharply in the following 1–2 h of haemostatic resuscitation and decline continuously thereafter, suggesting an important role for the treatment administered [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
“…Between June 2012 and July 2021, a total of 328 predominantly male (75.3%) subjects fulfilled the inclusion criteria (Figure 1). The mean age was 53 (37-68 IQR) years, the median ISS was 29 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). According to the predefined criteria, there were 72 patients in the isolated traumatic brain injury group (TBI group), 141 patients in the group of major trauma without TBI (MT group), and 115 patients in the group of major trauma with additional TBI (MT + TBI group).…”
Section: Demographic and Clinical Datamentioning
confidence: 99%
“…A low platelet count in severely injured patients is associated with poor outcome in both isolated TBI and polytrauma [28,29]. However, the platelet count does not provide any meaningful information about the platelet function.…”
Section: Platelet Function and Injury Patternmentioning
confidence: 99%
“…These hemostatic strategies of resuscitation with balanced ratios of RBC:plasma and RBC:platelets lead to earlier correction of coagulopathies and lower hemorrhagerelated mortality in injured patients requiring large volume transfusion [33][34][35][36][37][38]. Both the timing and ratios of blood products are important, as early platelet transfusion within the first 6 h after injury has been shown to be most beneficial to hemostasis and mortality, both in combat and civilian populations [39][40][41][42][43][44][45]. A recent study of the American College of Surgeons Trauma Quality Improvement Program (TQIP) database demonstrated that unbalanced platelet:RBC transfusion ratios are common with nearly twice as many patients receiving unbalanced ratios, which portended worse odds of mortality than unbalanced plasma:RBC transfusion ratios.…”
Section: Hemostatic Resuscitation In Traumamentioning
confidence: 99%